Alternative approaches to forecasting currency demand in the Jamaican economy - Williams, Claney E. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1997)
Addresses the shortfalls in forecasting the monthly currency issue. Pressents a more scientific approach to formalize the forecasting techniques currently being used.